Biology Learning Innovation: Utilization of Ethnobotanical Knowledge in Pandan (Pandanus tectorius) Craft Production by the Kerinci Community - Okti, Relan; Kencanawati, Indah; M, Novinovrita. (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2024)
Etnobotany is focused on using pandan plants in making handicrafts as part of the community's culture. This research was conducted in Rawang Village, Hamparan District. Rawang District, Sungai Penuh Regency, Full City, which combines ethnobotany knowledge in the process of making handicrafts by utilizing pandan plants. This study aims to explore the traditional knowledge of local people about the use of pandan plants in making handicrafts. The research method used is a qualitative approach with a descriptive method, including observation, in-depth interviews, and documentation. The study results showed eight stages in the process of making pandan. lapik crafts, namely sorting leaves, sewing or separating leaves into several parts, removing thorns, softening, coloring, drying, and weaving. With their flexibility and diversity, Pandan plants have quite a kiss of economic and cultural potential. Crafts from pandan plants, such as pandan lapiak, reflect technical skills, enrich local cultural heritage, and increase environmental awareness. The use of pandan plants as a learning medium can teach cultural values, traditional skills, and awareness of environmental sustainability to the younger generation.